Peekity boo what you can do! - Roemer, Heidi (Henry Holt and Company, 2019)
Rhyming text follows a toddler's bedtime routine, from an energetic bath to choosing jammies, reading a book, cuddling with a favorite toy, and snuggling with loved ones before gently falling asleep.